Admission Mean Platelet Volume and Poor Functional Outcome After Reperfusion Therapy for Acute Ischaemic Stroke: A Systematic Review and Meta-Analysis - Ivan Agusta Dwi Kristiawan; Kumara Tini; Ida Ayu Sri Wijayanti; Anak Agung Ayu Putri Laksmidewi; Ketut Widyastuti; Ni Putu Ayu Putri Mahadewi (Sriwijaya Journal of Neurology, 2026)
Background: Mean platelet volume (MPV), an inexpensive index of platelet activation from the routine admission full blood count, has been linked to poor outcome in unselected ischaemic stroke, but its prognostic value in reperfusion-treated patients is uncertain and conflicting. Objective: To quantify the association between admission MPV and poor functional outcome after reperfusion therapy, and to test whether it depends on treatment modality and MPV operationalisation. Methods: PubMed was searched for cohort or case–control studies reporting admission MPV against poor functional outcome (modified Rankin Scale 3–6) in adults with acute ischaemic stroke treated with intravenous thrombolysis and/or mechanical thrombectomy. Odds ratios (OR) were pooled using DerSimonian–Laird random-effects models, with a-priori subgroups by modality and MPV metric and leave-one-out, adjusted-only and Hartung–Knapp sensitivity analyses. This review was not registered in a public registry. Results: Ten studies were included and seven (1,597 patients) pooled. Higher MPV was associated with poor outcome (OR 1.62, 95% CI 1.22–2.16; I²=68.5%). The effect was strong with dichotomised MPV after thrombectomy (OR 2.56, 95% CI 1.60–4.08) but modest with continuous or quartile MPV in broad reperfusion (OR 1.27, 95% CI 1.08–1.49); the between-subgroup difference was significant (p=0.005) yet not robust to removing the most weighted study per arm. Conclusion: Higher admission MPV was associated with poor functional outcome after reperfusion therapy, but its magnitude depended on modality and measurement; certainty was low (GRADE). MPV is a promising, essentially free supplementary marker best used within multivariable models, requiring confirmation in standardised prospective studies.